Promoter CpG island methylation of RET predicts poor prognosis in stage II colorectal cancer patients. Issue 3 (2nd February 2014) - Draht, Muriel X.G.; Smits, Kim M.; Tournier, Benjamin; Jooste, Valerie; Chapusot, Caroline; Carvalho, Beatriz; Cleven, Arjen H.G.; Derks, Sarah; Wouters, Kim A.D.; Belt, Eric J.T.; Stockmann, Hein B.A.C.; Bril, Herman; et al.
Abstract : Improved prognostic stratification of patients with TNM stage II colorectal cancer (CRC) is desired, since 20–30% of high‐risk stage II patients may die within five years of diagnosis. This study was conducted to investigate REarranged during Transfection ( RET ) gene promoter CpG island methylation as a possible prognostic marker for TNM stage II CRC patients. The utility of RET promoter CpG island methylation in tumors of stage II CRC patients as a prognostic biomarker for CRC related death was studied in three independent series (including 233, 231, and 294 TNM stage II patients, respectively) by using MSP and pyrosequencing. The prognostic value of RET promoter CpG island methylation was analyzed by using Cox regression analysis. In the first series, analyzed by MSP, CRC stage II patients ( n = 233) with RET methylated tumors had a significantly worse overall survival as compared to those with unmethylated tumors (HRmultivariable = 2.51, 95%‐CI: 1.42–4.43). Despite a significant prognostic effect of RET methylation in stage III patients of a second series, analyzed by MSP, the prognostic effect in stage II patients (n = 231) was not statistically significant (HRmultivariable = 1.16, 95%‐CI 0.71–1.92). The third series (n = 294), analyzed by pyrosequencing, confirmed a statistically significant association between RET methylation and poor overall survival in stage II patients (HRmultivariable = 1.91, 95%‐CI: 1.04–3.53). Our results show that RET promoter CpG island methylation, analyzed by two different techniques, is associated with a poor prognosis in stage II CRC in two independent series and a poor prognosis in stage III CRC in one series. RET methylation may serve as a useful and robust tool for clinical practice to identify high‐risk stage II CRC patients with a poor prognosis. This merits further investigation. Highlights: RET methylation predicts poor prognosis for TNM stage II colorectal cancer patients. The poor prognosis in stage II patients is independent of MSI, CIMP and BRAF status. RET methylation can be detected by MSP and pyrosequencing. RET methylation can be detected in fresh‐frozen and FFPE tissue. RET methylation may serve as a robust biomarker in clinical practice.